ADSORPSI ZAT WARNA BIRU METILENA OLEH LEMPUNG BENTONIT AKTIF - -, Susilawati (Universitas Andalas, 2014)
Â ABSTRACTStudy on bentonite adsorbent properties such as benthonite optimum activation condition, afectof sulfic acid consentration, activation temperature and activation time to decolorization ofmethilne Blue has been conducted. The study was started by activation of bentonite uponmethylene blue. The data was analysis by statistical method : Least Significant Difference (LSDor BNT). It is found that the mass of bentonite significantly effected (P < 0,01) on thedecolorization percentage of methylene blue. The optimum condition of adsorbtion showed thatthe concentration of activating agent (sulfic acid) was 20%, activation temperature at 110o C andactivation time was 30 minutes. On this optimum condition, the bentonite absorbed methyleneblue up to 93.30% .Keywords: Bentonite, Methylene Blue, Activation, Decolorization